Antara dua darjat dan seniman bujang lapok: the analysis of songs and mise en scene from auteur cinemusic’s perspective / Luqman Mohd Oslan - Mohd Oslan, Luqman (2020)
Film and music are performing arts that have long been linked together. This dissertation examines how P.Ramlee's style produces melodies in his songs in the film thus creating compatibility and effectiveness in his narrative and the audience who views it. Among his films discussed in this dissertation are Antara Dua Darjat and Seniman Bujang Lapok. P.Ramlee's songs are said to have become a favourite of many people in Malaysia and are considered a legend. This is due to the fact that his songs are very close to the listeners of the song and movie fans at the time. This study was conducted to identify the existence of three important elements, namely social class issues, cultural identity and is related to modernity and traditional in terms of song creation and mise en scene of the film. Using the Auteur Theory approach (Auteur Theory) and Musical Analysis / Mise en scene / Cinematography as a theoretical framework, this study attempts to understand the perspective and point of view of P.Ramlee as a melomane auteur through the music he composed through songs as depicted in films as a whole.